ZIRABAD LOCAL LORE MUSEUM - Uktamali Rustam ugli, Ravshanov (PT. Antis International Publisher, 2025)
Objective: This study explores the establishment and significance of the Zirabad Local Lore Museum, a specialized institution dedicated to preserving and showcasing the historical and cultural heritage of a specific regional community. Method: A qualitative descriptive approach was employed to analyze the museum’s structure, thematic focus, and ethnographic elements through literature review and comparative analysis of similar regional museums. Results: The findings highlight that the museum serves as a valuable resource for ethnotourism, presenting the local community’s lifestyle, customs, rituals, crafts, and cultural identity in a coherent narrative. Its regional specificity enhances its appeal to both local and international tourists seeking authentic cultural experiences. The museum also contributes to cultural preservation and community engagement. Novelty: While local lore museums are often overlooked in mainstream museology, this article positions the Zirabad Local Lore Museum as a unique case that bridges regional identity with global cultural discourse, thereby offering a new perspective on the role of micro-level heritage institutions in international tourism and heritage education.